ANÁLISE DE ESCAMAS DE PEIXES PARA MONITORAMENTO AMBIENTAL POR ESPECTROSCOPIA DE PLASMAINDUZIDA POR LASER (LIBS) - DA COSTA SHIMADA, Julia Thiemy; SOUZA, Bianca de Andrade; ANDRADE, Luis Humberto da Cunha; LIMA JÚNIOR, Sidnei Eduardo (ANAIS DO ENIC, 2024)
-